Determination of Seepage Rate Through Senggarang Coastal Embankment - AZAHARRUDIN, MUHAMMAD ASYRAF; MOHD ARISH @ ARSHAD, NUR AINI (Progress in Engineering Application and Technology, 2023)
In the Malaysian state of Johor, the Senggarang Coastal Embankment is situated in the Batu Pahat area. There is approximately 10 kilometers of coastline, this part of coastline was then divided into 21 points but only one until 13 will be cover in this study are to be analyzed. Senggarang Coastal Embankment has serious seepage and overtopping issues that have damaged the service road, caused flooding on the inland side during high tides, and are likely to fail soon. This could jeopardize stability and increase the risk of the earth bund collapsing. When seepage-related inland flooding occurs, saltwater invasion can result, causing harm to surrounding crops and the loss of productive land. The main research objectives are to determine severe seepage location on Senggarang Coastal Embankment (SCE) and also to monitor and record seepage and compare with tidal effect pattern. Seepage rate was use to calculated the total seepage that flow into the inland by using traditional Piezometer test and Probe Mackintosh. Based on the information that was gathered, the seepage is caused by the tides. At SCE, the Mackintosh Probe has been used to find out how strong the soil is by measuring how many blows it can take before breaking. Probe Mackintosh's results point to a possible place where seepage could leave SCE. Therefore, the result obtained proves that seepage condition at SCE is critical and needed serious provision from responsible party and using compacting soil to increase the value of bearing capacity.